Student experience with remote teaching during the SARS-COV-2 pandemic in a university center - Stanziola de Moraes, Gabriel (2024)
The COVID-19 pandemic promoted the need for social distancing, which, in turn, forced educational institutions to adopt technologies that allowed the continuation of face-to-face studies, in a safer way, in the remote modality. The adaptation to this format had to be fast. Thus, this study aimed to understand the perception of students from a university center in the rural area of São Paulo. The participants were invited by email to answer a self-administered online questionnaire about their experience during the adoption of this emergency measure by institution. This questionnaire included objective questions involves, for example, the perception of their skills in using virtual platforms and impact on mental health and academic performance. In a qualitative way, questions were raised about benefits and challenges of implementing remote teaching. Varied perceptions were found, indicating that there were benefits in the implementation of the virtual modality, but also that there were points to be improved.